2014
DOI: 10.1128/aac.02321-13
|View full text |Cite
|
Sign up to set email alerts
|

Resurrecting Inactive Antimicrobial Peptides from the Lipopolysaccharide Trap

Abstract: Host defense antimicrobial peptides (AMPs) are a promising source of antibiotics for the treatment of multiple-drug-resistant pathogens. Lipopolysaccharide (LPS), the major component of the outer leaflet of the outer membrane of Gram-negative bacteria, functions as a permeability barrier against a variety of molecules, including AMPs. Further, LPS or endotoxin is the causative agent of sepsis killing 100,000 people per year in the United States alone. LPS can restrict the activity of AMPs inducing aggregations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 70 publications
4
47
0
Order By: Relevance
“…It is observed that in the control simulation, the LG21 peptide is majorly found as a random coil structure. Previous experimental studies based on NMR and CD-spectra also observed that LG21 is a hybrid antimicrobial peptide that exists in a random-coil conformation in aqueous solution [29,30]. From Table 1, it is also observed that for the simulation system with Psl, the percentage of α-helix (≈0.26) is substantially higher than the one observed in the control simulation (≈0.05), which clearly demonstrates that interaction of LG21 with Psl induces the helicity.…”
Section: Molecular Dynamics (Md) Simulation Of Psl-lg21 Binding Modementioning
confidence: 51%
“…It is observed that in the control simulation, the LG21 peptide is majorly found as a random coil structure. Previous experimental studies based on NMR and CD-spectra also observed that LG21 is a hybrid antimicrobial peptide that exists in a random-coil conformation in aqueous solution [29,30]. From Table 1, it is also observed that for the simulation system with Psl, the percentage of α-helix (≈0.26) is substantially higher than the one observed in the control simulation (≈0.05), which clearly demonstrates that interaction of LG21 with Psl induces the helicity.…”
Section: Molecular Dynamics (Md) Simulation Of Psl-lg21 Binding Modementioning
confidence: 51%
“…Additionally, the outer membrane of Gram-negative organisms incorporates a negatively charged lipopolysaccharide (LPS) layer that acts as a molecular sieve, impeding the passage of small molecules across the cellular envelope. The protective effect of the Gram-negative OM to certain antibiotics is well documented (17,(22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
“…The tight packing of the six fatty acid components of lipid A of the LPS layer is thought to underlie the impervious nature of the Gram-negative OM (23,24). A range of E. coli mutants, which have profound defects in the lipid A component of the LPS in the OM, have a phenotype that is described as deep rough.…”
Section: Resultsmentioning
confidence: 99%
“…Recent insights into AMP interactions with LPS indicate that binding to the bacterium's outer membrane does not guarantee the peptide subsequent membrane-permeabilizing action. On the contrary, LPS may induce peptide aggregation at the cell wall, acting as an inactivating trap and impeding access to the cytoplasmic membrane (59). Indeed, a recent biophysical approach toward the underlying AMP structural requirements for biofilm eradication pointed to a delicate balance between peptidebacterium adhesion and self-oligomerization (12).…”
Section: Discussionmentioning
confidence: 99%